Oogenesis 2012
DOI: 10.1007/978-0-85729-826-3_17
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus Cell Gene Expression as a Marker of Oocyte Quality

Abstract: Cumulus cells (CCs) are a highly specialized cell type that surround the mammalian oocyte from antrum formation to the early stages of embryo development in the oviduct. During this period of close vicinity, CCs maintain paracrine and cell-to-cell communications with the oocyte. The increasing use of CCs to predict oocyte quality requires a growing understanding of their involvement in oocyte developmental competence acquisition. This chapter highlights the current knowledge about CC differentiation and commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 226 publications
(257 reference statements)
0
4
0
Order By: Relevance
“…By interacting with oocyte-derived factors (44,48,49), EGF-like proteins activate the EGF receptor to engage the MAPK pathway for meiotic resumption, with COC expansion in response to cyclo-oxygenase 2 (COX2), gremlin1 (GREM1), hyaluronic acid synthase 2 (HAS2), and pentraxin 3 (PTX3) as down-stream GDF-9 target genes (46,50). The net result is an oocyte that can undergo GV breakdown to produce a haploid metaphase II oocyte (i.e., nuclear maturation) and is capable of cytoplasmic maturation, fertilization, and embryonic development (44,51,52).…”
Section: Oocyte Maturationmentioning
confidence: 99%
“…By interacting with oocyte-derived factors (44,48,49), EGF-like proteins activate the EGF receptor to engage the MAPK pathway for meiotic resumption, with COC expansion in response to cyclo-oxygenase 2 (COX2), gremlin1 (GREM1), hyaluronic acid synthase 2 (HAS2), and pentraxin 3 (PTX3) as down-stream GDF-9 target genes (46,50). The net result is an oocyte that can undergo GV breakdown to produce a haploid metaphase II oocyte (i.e., nuclear maturation) and is capable of cytoplasmic maturation, fertilization, and embryonic development (44,51,52).…”
Section: Oocyte Maturationmentioning
confidence: 99%
“…Studies indicated that in vitro-matured bovine oocyte has different gene expression patterns in vitro (22,23). Gene expression patterns of the cumulus and oocytes have been considered as the molecular markers of the oocyte quality (24). Our results demonstrate that the IVM procedure affects the development gene expression profile of cattle oocytes.…”
Section: Discussionmentioning
confidence: 62%
“…However, adiponectin decreased insulin-induced steroidogenesis and increased IGF-1-induced proliferation of cultured granulosa cells through a potential involvement of ERK1/2 MAPK pathway [14]. Also, previous studies have confirmed that the changes in the expression levels of some genes in cumulus cells are highly correlated with the future developmental competence of the enclosing oocytes so that they are considered as markers of the oocyte quality [15,16]. Therefore, the current research was designed to investigate the in vitro effects of *Corresponding author: Mojtaba Kafi, Department of Animal Reproduction, School of Veterinary Medicine, Shiraz University, Shiraz, Iran, Tel: 0098-9131709008; E-mail: kafi@shirazu.ac.ir adiponectin at physiologic concentrations found in the follicular fluid of the pre-ovulatory bovine ovarian follicle on 1) the bovine in vitro oocyte nuclear maturation and cumulus expansion rates, 2) the early development of bovine embryos in vitro, 3) the expression profiles of adiponectin receptors and some developmentally important marker genes in the cumulus cells and 4) the expression rates of the two most important oocyte secreted factors: Bmp15 and Gdf9.…”
Section: Introductionmentioning
confidence: 99%